English English - Awaliyah Alifi (Jurnal Ilmiah Ekonomi Islam, 2025)
This paper aims to see how major the effect of cash waqf and pesantren facility utilization towards Pesantren’s economic empowerment, using case study approach to Indonesian pesantren. The data in this research are gathered through questionnaire and literature research through related topics. Questionnaire are answered by pesantren administrator from different institutions and will be analyse with a Partial Least Square (PLS) to see how big the influence of cash waqf and pesantren facilities on the factors related. This study finds that cash waqf played a significant role in Pesantren Economic Empowerment while supporting facility that reliable simply assets and business incubator, meaning the existence of capital to start pesantren’s entreprises is essential furthermore supported with assets and conducive atmosphere will resulting a faster growth of Pesantren economic empowerment. This research highlight the importance of cash waqf and facility for Pesantren economic empowerment, cash waqf seen as a more flexible, accessible, and practical source of fund. Keywords: Awqaf, Cash waqf, Waqf, Pesantren, Pesantren facility, Pesantren empowerment, Pesantren economic empowerment, Pesantren entreprises